Effects of micronutrients foliar application on rice (Oryza Sativa L. cv. Shiroodi) morphological traits, yield and yield components - Daneshtalab Lahijani, Ashkan; Mosavi, Amir Abbas; Moballeghi, Morteza (International Journal of Agricultural and Biological Engineering, 2020)
In order to assess the effect of micronutrients (Mn, Zn, Fe, Cu and B) on rice metabolism and performance, research implemented in the form of randomized complete block design with 8 treatments (T0 Control, T1-T7 one to seven spraying) with 3 replications. The location of this research was the Rice Research Institution of Iran (Mazandaran) during two consecutive years (2017 and 2018 cultivation seasons). The results demonstrate that the effect of micronutrients foliar application is significant at the 1% level of probability of some traits such as plant wet weight, 12 plants yield, and leaf area. Also, it is significant at the 5% level of probability of some traits such as the number of tillers/plant, 80 plants yield, cluster length, leaf color chart and 1000 grains weight. In this relation, the interaction of year*foliar application was significant for the studied traits. The purpose of this study was to evaluation of micronutrients effect on rice plant. Pursuant to the results, it can be significantly concluded that the micronutrients furnish through the leaf application can influence on rice yield and yield components. This event is justifiable by micronutrients role in the plant metabolic procedures and enzymes activation that affects crops vegetative growth and productivity. Furthermore, the postponement time can be decreased by the leaf spraying of the micronutrients and this is vital for rice plant during the rapid growth phase. The results are significantly evident that one leaf spraying of essential micronutrients will impress on rice yield. Keywords: grain yield, foliar application, micronutrients, rice (Oryza Sativa L.) DOI: 10.25165/j.ijabe.20201301.5272 Citation: Daneshtalab Lahijani A, Mosavi A A, Moballeghi M. Effects of micronutrients foliar application on rice (Oryza Sativa L. cv. Shiroodi) morphological traits, yield and yield components. Int J Agric & Biol Eng, 2020; 13(1): 217–223.